2008
DOI: 10.1002/j.0022-0337.2008.72.11.tb04615.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative Analysis of Student Feedback on ePortfolio Learning

Abstract: At the University of British Columbia, we introduced an ePortfolio assignment in the operative dentistry clinical simulation module and conducted a pilot study to explore the usefulness of ePortfolios as a learning tool for dental students. Qualitative assessments included student self-reflections on the ePortfolio experience. In the quantitative evaluation, ePortfolio learning was hypothesized as a multidimensional experience with four dimensions: 1) an ePortfolio experience is valuable for learning operative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…In addition to prompting self‐assessment, portfolios have also been found to support competency‐based evaluation of trainee performance in medical education 31 . Online portfolios, known as ePortfolios, provide additional flexibility as students may access them remotely or even on a mobile device, and faculty may provide real‐time feedback to enhance student learning 32 . Previous studies have shown that ePortfolios’ capacity for reflection and the utility of feedback provided can vary based on whether students and faculty members perceive the ePortfolio to be accessible, easy‐to‐use, and requiring an appropriate amount of time to complete 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to prompting self‐assessment, portfolios have also been found to support competency‐based evaluation of trainee performance in medical education 31 . Online portfolios, known as ePortfolios, provide additional flexibility as students may access them remotely or even on a mobile device, and faculty may provide real‐time feedback to enhance student learning 32 . Previous studies have shown that ePortfolios’ capacity for reflection and the utility of feedback provided can vary based on whether students and faculty members perceive the ePortfolio to be accessible, easy‐to‐use, and requiring an appropriate amount of time to complete 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Given that, online communication is here to stay , blended learning, which combines a face‐to‐face and an online teaching approach, allows greater flexibility in learning . E‐technologies, such as blogs or wikis, make new demands on learning and provide new supports to learning, even as they dismantle some of the learning supports upon which education has depended in the past . Wikis, blogs or e‐portfolios enable students to explore creative possibilities in presenting their work, but wikis also enable students to work collaboratively in a group in an online environment with access to peer learning opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the traditional teaching/learning synchronous model, the teaching of Microbiology at FMDUP incorporated the use of Moodle Virtual Learning Environment (MVLE) within the course organisation . This approach of blended learning, with synchronous and asynchronous levels of education, revealed to be of great value for the teaching of dental students . This approach follows the Association for Dental Education in Europe's (ADEE) recommendations, which suggests that the student learning is probably best facilitated by the use of a combination of educational methods and tools that promote reflection, critical thinking and continued learning, for example the use of self‐ or peer assessment and portfolios .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, drawing on multiple theoretical perspectives, including dialogical self theory and broader sociocultural perspectives, can support a more nuanced interrogation of the role ePortfolios can play in supporting students to develop the necessary knowledge, skills, and dispositions for professional life. Further, from a methodological point of view, integrating qualitative and quantitative approaches can provide a richer and more multifaceted understanding of how ePortfolios are conceived and used by students (Gardner & Aleksejuniene, ).…”
Section: Introductionmentioning
confidence: 99%